DEALING WITH DIVERSITY: Thematic Interpretation on “Defending Islam” - Ali Ja'far (AL ITQAN: Jurnal Studi Al-Qur'an, 2018)
Modern Indonesian had featured by two overlapping terms ‘Defending Religion’ and ‘Defending Islam’. Both are similar and popular term during the light of Islamic resurgence in the post-reformation era. As the term emerged publicly, religious discourse and debate concerning on the term are inevitable. The term, problematically, used by the particular group to legitimate numerous political actions, escalated the number of religious blasphemy. Surely, Muslims are obligated to defend Islam, but Islamic teaching also encourages the Muslim to respect communal-pluralistic society. By employing a thematic approach, this paper then argues that the idea of ‘defending religion’ should be revisited. Based on the occasion of revelation, the collected verses initially considered as an appeal to do “justice” (ʽadl), fight against the repressive community, persecution, displacement, and any outraged acts. Through tracing the occasion of revelation, this paper also argued that the idea of “defending religion” has also much to do with the idea of “defending diversity” in the context of pluralistic society.